Field and geochemical evidence of cretaceous anoxic events in parts of the Northern Benue Trough, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
Field and geochemical evidences presented in this study report the occurrence of Cretaceous anoxic events in the Northern Benue Trough, Nigeria. Five Cretaceous formations (Bima, Yolde, Pindiga, Dukul, and Fika) within the Northern Benue Trough were investigated, and the field evidences reveal the occurrence of dark-colored, finely laminated shale units lacking bioturbation, which are mostly associated with coarsening upward sequences. This is typical of sediments deposited under transgressive waters with prevailing anoxic conditions which were ubiquitous during the Cretaceous. Furthermore, total organic carbon values obtained from the geochemical analyses of the dark shales were considerably high, ranging from 1.35% as the lowest value to 3.67% as the highest value, consistent with concentrations of organic matter preserved due to the anoxic condition of deposition, while the sulfur content of the studied samples were found to fall within ranges below 1% (the highest being just about 0.6%). Rock-eval pyrolysis data obtained for the studied samples suggest kerogen types III and IV, implying organic materials derived from either continental or mixed continental and marine depositional environments. Tmax data obtained shows that most of the studied shales are thermally immature, implying a negligible to poor hydrocarbon generation potential.